Surface engineering of silica nanoparticles for oral insulin delivery: characterization and cell toxicity studies - Andreani, Tatiana; Kiill, Charlene P. [UNESP]; Souza, Ana Luiza R. de [UNESP]; Fangueiro, Joana F.; Fernandes, Lisete; Doktorovova, Slavomira; Santos, Dario L.; Garcia, Maria L.; Gremiao, Maria Palmira D. [UNESP]; Souto, Eliana B.; Silva, Amelia M. (Elsevier B.V., 2014)
The present work aimed at studying the interaction between insulin and SiNP surfaced with mucoadhesive polymers (chitosan, sodium alginate or polyethylene glycol) and the evaluation of their biocompatibility with HepG2 and Caco-2 cell lines, which mimic in vivo the target of insulin-loaded nanoparticles upon oral administration. Thus, a systematic physicochemical study of the surface-modified insulin-silica nanoparticles (Ins-SiNP) using mucoadhesive polymers has been described. The surfacing of nanoparticle involved the coating of silica nanoparticles (SiNP) with different mucoadhesive polymers, to achieve high contact between the systems and the gut mucosa to enhance the oral insulin bioavailability. SiNP were prepared by a modified Stoner method at room temperature via hydrolysis and condensation of tetraethyl orthosilicate (TEOS). Interaction between insulin and nanoparticles was assessed by differential scanning calorimetry (DSC), X-ray and Fourier-transform infrared (FTIR) studies. The high efficiency of nanoparticles'coating resulted in more stable system. FTIR spectra of insulin-loaded nanoparticles showed amide absorption bands which are characteristic of alpha-helix content. In general, all developed nanoparticles demonstrated high biocompatible, at the tested concentrations (50-500 mu g/mL), revealing no or low toxicity in the two human cancer cell lines (HepG2 and Caco-2). In conclusion, the developed insulin-loaded SiNP surfaced with mucoadhesive polymers demonstrated its added value for oral administration of proteins. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Silica nanoparticles; Coated-SiNPs; Insulin; Mucoadhesive polymers; HepG2 cell; Caco-2 cell